1998
DOI: 10.1111/j.1744-6570.1998.tb00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Trait, Rater and Level Effects in 360‐degree Performance Ratings

Abstract: Method and trait effects in multitrait-multirater (MTMR) data were examined in a sample of 2,350 managers who participated in a developmental feedback program. Managers rated their own performance and were also rated by two subordinates, two peers, and two bosses. The primary purpose of the study was to determine whether method effects are associated with the level of the rater (boss, peer, subordinate, self) or with each individual rater, or both. Previous research which has tacitly assumed that method effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
209
5
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(233 citation statements)
references
References 45 publications
15
209
5
4
Order By: Relevance
“…Mount, Judge, Scullen, Sytsma, & Hezlett, 1998;Viswesvaran et al, 2002). Thus, although this process is plausible, it is not consistent with the empirical evidence.…”
Section: Diagnostic Steps In Disentangling Construct-level Differencementioning
confidence: 38%
See 2 more Smart Citations
“…Mount, Judge, Scullen, Sytsma, & Hezlett, 1998;Viswesvaran et al, 2002). Thus, although this process is plausible, it is not consistent with the empirical evidence.…”
Section: Diagnostic Steps In Disentangling Construct-level Differencementioning
confidence: 38%
“…Bracken et al (p. 765), despite academic research (Mount et al, 1998) clearly showing that it might be better from a true-score measurement perspective to combine ratings from naturally occurring work groups (peers, supervisors, etc. ), argue that "a true 360°feedback assessment, under our definition, must be designed in such a way that differences in rater perception are clearly identified and meaningful comparisons can be made between perceptions of different rater groups, agreement (or lack thereof) within a rater group, and even individual raters (e.g., self, manager) where appropriate.…”
Section: Construct-level Disagreements and Rater Reliability In Supermentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, since employees' performance appraisal causes some conflict and opposition between administrators and employees, leading to the employees' exhibiting some deviant behaviors, supervisors treat them leniently, giving them high scores in order to prevent such conflicts (Spector, 2002;Decenzo and Robbins, 1996). Along with this issue, approximately 90 years ago, Thorndike (1920 cited in Mount et al,1998) observed that whenever administrators evaluate their employees' performances, the correlation between dimensions of work performance was higher that what was in reality. The studies conducted on this issue have shown that the effects of performance appraisal method are one the most major sources of error in rating performances.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, research based on observational studies of managerial work (Kotter, 1982;Luthans, 1988;Mintzberg, 1973) established several managerial functions (e.g., planning, controlling), and interpersonal activities such as communicating and getting input from and providing feedback to others. Using Mann's (1965) conceptualizations, research examining the ratings of managerial effectiveness (e.g., Mount, Judge, Scullen, Sytsma, & Hezlett, 1998) identified three competence categories: administrative, human relations, and technical. Finally, social cognitive theory elaborates on the managerial importance of self-regulatory mechanisms such as selfawareness (Bandura, 1999;Stajkovic, 2003;Wood & Bandura, 1989).…”
Section: Methodsmentioning
confidence: 99%